Electric properties of TlInS₂ single crystals - Mustafaeva, S.N.; Ismailov, A.A.; Akhmedzade, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Injection currents are studied in high-resistive layer of TlInS2 single crystals and the following parameters were determined: equilibrium concentration of charge carriers in the allowed band p0 = 1.67⋅10¹⁰ cm⁻³; concentration of traps Nt = 10¹²cm⁻³; capture factor θ = 0.17; mobility of charge carriers μ = 3.3⋅10⁻³cm²/V⋅s; the depth of trap level responsible for the injection current Et = 0.44 eV.